1995
DOI: 10.1183/09031936.95.08030357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of altitude on urinary leukotriene (LT) E4 excretion and airway responsiveness to histamine in children with atopic asthma

Abstract: E Ef ff fe ec ct t o of f a al lt ti it tu ud de e o on n u ur ri in na ar ry y l le eu uk ko ot tr ri ie en ne e ( (L LT T) ) E E 4 4e ex xc cr re et ti io on n a an nd d a ai ir rw wa ay y r re es sp po on ns si iv ve en ne es ss s t to o h hi is st ta am mi in ne e i in n c ch hi il ld dr re en n w wi it th h a at to op pi ic c a as st th hm ma a Subjects were randomly divided into two groups. Measurements of baseline forced expiratory volume in one second (FEV 1 ), the concentration of histamine producing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
2
15
0
4
Order By: Relevance
“…Simon et al [37] studied 14 HDM-allergic asthmatic children and showed an improvement of lung function and reduction of peripheral blood eosinophils after 3 weeks at high altitude in Davos. Christie et al [38] performed a randomized-controlled study in Dutch children who were staying at the Asthma Centre in Davos for at least 1 month, and returned home for a short period of 2 weeks. As compared with the children who remained in Davos, the children who returned from the Netherlands showed a significant decline in FEV 1 , an increase in airway responsiveness to histamine, accompanied by a threefold increase in urinary leukotriene E 4 (LTE 4 ).…”
Section: High-altitude Treatment In Children With Allergic Asthmamentioning
confidence: 99%
“…Simon et al [37] studied 14 HDM-allergic asthmatic children and showed an improvement of lung function and reduction of peripheral blood eosinophils after 3 weeks at high altitude in Davos. Christie et al [38] performed a randomized-controlled study in Dutch children who were staying at the Asthma Centre in Davos for at least 1 month, and returned home for a short period of 2 weeks. As compared with the children who remained in Davos, the children who returned from the Netherlands showed a significant decline in FEV 1 , an increase in airway responsiveness to histamine, accompanied by a threefold increase in urinary leukotriene E 4 (LTE 4 ).…”
Section: High-altitude Treatment In Children With Allergic Asthmamentioning
confidence: 99%
“…51 As a marker of inflammatory response, eight patients with asthma and a mean age of 14 years who returned to an altitude of 1560 m after a 14 day break at sea level, showed increases in airway reactivity and inflammatory mediators, compared to controls who stayed at altitude. 52 More recently, it has been shown that genetic factors may play an important role in protection against the effects of altitude. The presence of a specific angiotensin converting enzyme (ACE) genotype (I allele), resulting in low ACE activity, is associated with protection of SaO 2 levels in climbers who ascend rapidly to over 5000 m. 53 In addition, climbers susceptible to high altitude pulmonary oedema were more likely to have certain genetic markers associated with low levels of nitric oxide production in the lung.…”
Section: Susceptibility To Altitude Problemsmentioning
confidence: 99%
“…High-altitude treatment has been applied for decades in patients with asthma, especially in children and adolescents with moderate-tosevere atopic disease [6][7][8][9]. The success of this treatment has long been attributed to the absence of house dust mite allergens at altitudes .1,600 m [10].…”
mentioning
confidence: 99%